Prevalence and Possible Role of Candida Species in Patients with Psoriasis: A Systematic Review and Meta-Analysis - Aldona Pietrzak; Ewelina Grywalska; Mateusz Socha; Jacek Roliński; Kinga Franciszkiewicz-Pietrzak; Lidia Rudnicka; Marcin Rudzki; Dorota Krasowska (Mediators of Inflammation)
Although fungal colonization is implicated in the pathogenesis of psoriasis, its prevalence remains unclear. The aim of this systematic review and meta-analysis was to provide an overview on the prevalence of Candida species in patients with psoriasis. We searched databases (MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and http://clinicaltrials.gov) to identify studies involving subjects of any age with an established diagnosis of psoriasis and healthy controls, who were tested for carriage of Candida spp. on the skin or mucosal membranes (or saliva and stool), or presented with clinical candidiasis with microbiologically confirmed etiology. We identified nine cross-sectional studies including a total of 1038 subjects with psoriasis (psoriatics) and 669 controls. We found Candida species detection rates for psoriatics were significantly higher than those in the controls, especially in the oral mucosa milieux. These results suggest psoriasis may be one of the systemic diseases that predispose to oral Candida spp. carriage and infection.